Nutritional Analysis of Morchella conica and its Role on Rural Livelihood - Magrati, Thakur P; Tripathee, Hari P; Devkota, Krishna P (Nepal Journal of Science and Technology, 2012)
The multipurpose Himalayan mushroom Morchella conica is one of the most popular wild high valued edible mushrooms throughout the world. It makes a good income generating source for rural livelihood. This study mainly focuses on the nutritional constituents of M. conica and its medicinal uses with social and financial values for rural livelihood. Nutritional analysis was conducted based on moisture, ash, crude fats, proteins and carbohydrates. The highest value of carbohydrate was 36.5% followed by protein 35.0%, crude fiber 28.8%, crude fat 12.0%, ash 8.2% and moisture 8.0%. In social and financial aspects of M. conica in the studied area, 20% ethnic groups involved for collection of this species. M. conica is economically high priced in which 60.0% poor and 53.3% medium class people are considering this to support their livelihood. The study also showed that this species is a potential source of diet and income for rural people. DOI: http://dx.doi.org/10.3126/njst.v12i0.6489 Nepal Journal of Science and Technology 12 (2011) 119-126